Preparation method and application of nitrogen-doped cobalt molybdate catalyst growing on CuO nanowire

By growing nitrogen-doped cobalt molybdate catalysts on CuO nanowires, the problems of low yield and high cost of electrocatalytic nitrate reduction to ammonia in the prior art are solved, and efficient, stable and economical ammonia production is achieved.

CN120155227APending Publication Date: 2025-06-17BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510282922.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

In the prior art, catalysts for electrocatalytic nitrate reduction to ammonia have problems of low yield and high cost, and it is difficult to meet the needs of industrial applications.

Method used

A nitrogen-doped cobalt molybdate catalyst (N-CoMoO4/CuO NW) grown on CuO nanowires was prepared by using the three-step wet chemistry method-hydrothermal-high temperature calcination method, and nitrate was reduced to ammonia under electrochemical conditions.

Benefits of technology

The ammonia production performance of the catalyst is significantly improved, and the ammonia yield of the catalyst reaches 1.45 mmol h-1 cm-2 or above, and has excellent catalytic stability and low preparation cost, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120155227A_ABST
    Figure CN120155227A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a nitrogen-doped cobalt molybdate catalyst growing on a CuO nanowire, and belongs to the technical field of ammonia preparation through electrochemical catalytic reduction. The preparation method comprises the following steps: preparing a Cu (OH) 2 nanowire by using a wet chemical method, then carrying out a hydrothermal reaction by using a mixed solution of sodium molybdate and cobalt nitrate, and finally calcining in an ammonia gas atmosphere to realize doping of nitrogen atoms so as to obtain the nitrogen-doped cobalt molybdate catalyst grown on the CuO nanowire. The nitrogen-doped cobalt molybdate catalyst grown on the CuO nanowire is used for treating nitrate in wastewater and converting the nitrate into ammonia with higher value. Under multiple actions of CuO nanowires and nitrogen atoms, the adsorption capacity of the surface of the catalyst to nitrate radicals is enhanced, cobalt molybdate serves as a carrier for providing hydrogen protons, the hydrogenation process of a nitrogen-containing intermediate is enhanced, and the efficiency of converting nitrate radicals into ammonia is improved. The preparation method is low in cost and high in operability and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalytic reduction of nitrate to ammonia, and particularly to a preparation method and application of a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires Background Art

[0002] Ammonia (NH3) is widely used in multiple production fields as an important chemical in the development of modern industry and agriculture, and is expected to become a new clean energy alternative to hydrogen in the future. The traditional method for synthesizing ammonia is the Haber-Bosch (H-B) nitrogen fixation method, but this process requires harsh conditions of high temperature and high pressure. Moreover, the annual energy consumption of the H-B nitrogen fixation method accounts for 1%-2% of the total global energy consumption, and the tail gas CO2 generated by industrial emissions accounts for 1.4% of the global total emissions. This process obviously does not meet the current vigorously advocated "dual carbon" goal. Therefore, it is of great significance to explore a green and efficient process for artificial ammonia synthesis. Nitrate (NO3 - ) as a main pollutant in industrial wastewater poses great harm to the ecological environment and human health. In recent years, the conversion of nitrate in wastewater into ammonia with high added value by using electrochemical reduction through the design of catalysts has attracted extensive attention of researchers. The characteristics of this method, which can be carried out under mild conditions, is green, safe and has low energy consumption, have made it a research hotspot. Noble metal catalysts have high yields but are expensive. Non-noble metal catalysts are inexpensive, but the characteristics of their yields have become the key points that need attention. Therefore, it is necessary to design a catalyst with low price and high yield for electrocatalytic nitrate reduction Summary of the Invention

[0003] To solve the problems existing in the prior art, the purpose of the present invention is to provide a preparation method and application of a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires. The prepared catalyst can achieve the improvement of the performance of electrocatalytic reduction of nitrate to ammonia, and has excellent Faraday efficiency and yield. Further, the method has low preparation cost, simple preparation process, and is expected to be applied industrially

[0004] To achieve the above purpose, the present invention provides the following technical solutions A preparation of a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires, comprising the following steps (1) Ultrasonically pretreat the copper foam with hydrochloric acid and wash it (2) Immerse the pretreated copper foam into a mixed solution of sodium hydroxide and ammonium persulfate to obtain Cu(OH)2 nanowires, i.e., Cu(OH)2 NW (3) Dissolve sodium molybdate dihydrate and cobalt nitrate hexahydrate in deionized water and stir to obtain a molybdenum-cobalt mixed solution (4) Transfer the molybdenum-cobalt mixed solution into the inner lining of a high-pressure reactor, vertically immerse the Cu(OH)2 nanowires therein, and conduct a hydrothermal reaction. After the reaction is completed, cool it to room temperature, take it out, and wash it to obtain a cobalt molybdate catalyst grown on the CuO nanowires, namely CoMoO4 / CuO NW; (5) Place the cobalt molybdate catalyst grown on the CuO nanowires in a tubular furnace, pre-pass ammonia gas, and keep it at 200 - 400 °C for heat preservation to obtain a nitrogen-doped cobalt molybdate catalyst grown on the CuO nanowires, namely N-CoMoO4 / CuO NW.

[0005] Further, in the step (1), the concentration of hydrochloric acid is 1 - 3 M, and the ultrasonic time is 10 - 20 min.

[0006] Further, in the step (2), the concentration of the sodium hydroxide solution in the sodium hydroxide and ammonium persulfate mixed solution is 4 - 6 M, and the concentration of the ammonium persulfate solution is 0.2 - 0.3 M; the soaking time in the sodium hydroxide and ammonium persulfate mixed solution is 20 - 40 min.

[0007] Further, in the step (3), the molar concentrations of sodium molybdate and cobalt nitrate in the molybdenum-cobalt mixed solution are equal, being (1.5 - 3.5) mmol / 35 ml.

[0008] Further, in the step (4), the temperature of the hydrothermal reaction is 120 - 160 °C, and the hydrothermal reaction time is 8 - 12 h.

[0009] Further, in the step (5), under an ammonia atmosphere, heat it to 200 - 400 °C at a rate of 5 °C / min and keep it for heat preservation for 1 - 3 h.

[0010] The method specifically is as follows: (1) Ultrasonically pretreat commercial copper foam with hydrochloric acid, and wash it 2 - 3 times with ethanol and deionized water; (2) Mix equal volumes of sodium hydroxide solution and ammonium persulfate solution, and stir it evenly with a magnetic stirrer to obtain a mixed solution; and immerse the commercial copper foam in (1) therein to obtain Cu(OH)2 nanowires, namely Cu(OH)2 NW (3) Dissolve sodium molybdate dihydrate and cobalt nitrate hexahydrate in deionized water, and stir it with a magnetic stirrer to obtain a mixed solution; (4) Transfer the mixed solution obtained in (3) into the inner lining of a high-pressure reactor, vertically immerse the Cu(OH)2 nanowires therein, then place the reactor in a high-temperature oven for hydrothermal reaction. After the reaction is completed, cool it to room temperature, take it out, and wash it 2 - 3 times with ethanol and deionized water to obtain a cobalt molybdate catalyst grown on the CuO nanowires, namely CoMoO4 / CuO NW; (5) Place the cobalt molybdate catalyst grown on the CuO nanowires in a tube furnace, pre-pass ammonia gas, and heat it to 300 °C at a rate of 5 °C / min under an ammonia atmosphere, then hold the temperature for 2 h to obtain the nitrogen-doped cobalt molybdate catalyst grown on the CuO nanowires, namely N-CoMoO4 / CuO NW.

[0011] Specifically, the area of the commercial copper foam in step (1) is 3×4 cm 2 , the thickness is 0.5 mm, the concentration of hydrochloric acid is 2 M, and the ultrasonic time is 15 min.

[0012] Specifically, the concentration of the sodium hydroxide solution in step (2) is 5 M, the concentration of the ammonium persulfate solution is 0.25 M, the mixing volume is 50 mL for both, and the soaking time is 30 min.

[0013] Specifically, the mass of sodium molybdate dihydrate in step (3) is 0.6048 g, the mass of cobalt nitrate hexahydrate is 0.7276 g, the volume of deionized water is 35 mL, the stirring rate of the magnetic stirrer is 600 r / min, and the stirring time is 5 min.

[0014] Specifically, the temperature of the hydrothermal reaction in step (4) is 150 °C, and the hydrothermal reaction time is 10 h.

[0015] The catalyst material is used to determine the reduction of nitrate to ammonia in the electrolyte.

[0016] The specific measurement steps are as follows: (1) Prepare a sodium hydroxide solution as the anolyte and a mixed solution of sodium hydroxide and sodium nitrate as the catholyte. The concentration of the sodium hydroxide solution is 1 M. In the mixed solution of sodium hydroxide and sodium nitrate, the concentration of sodium hydroxide is 1 M, and the concentration of sodium nitrate is 0.1 M.

[0017] (2) Add the above-prepared solutions to the H-type electrolytic cell twice for measurement. The specific measurement steps are as follows: Use Hg / HgO as the reference electrode and the catalyst prepared above as the cathode plate; assemble the cathode plate, anode plate, and reference electrode into a three-electrode electrolysis system. The cathode is filled with the catholyte, the anode is filled with an equal amount of the anolyte, turn on the switch of the electrochemical workstation, set the electrolysis voltage, and continuously react for 30 min. After the reaction is completed, measure the absorbance by indophenol blue spectrophotometry to obtain the ammonia concentration in the electrolyte, and calculate the Faraday efficiency and ammonia production rate.

[0018] Furthermore, the anode plate is a catalytic material with the ability to drive the oxygen evolution reaction, such as a platinum sheet, platinum mesh, nickel foam, etc., but not limited to these. Preferably, the anode plate is a platinum sheet.

[0019] Further, the catholyte is one of common aqueous electrolytes such as sodium hydroxide and sodium nitrate, potassium hydroxide and sodium nitrate, sodium sulfate and sodium nitrate, etc., but not limited thereto. The catholyte is a mixed solution of sodium hydroxide and sodium nitrate.

[0020] Further, the anolyte is one of common alkaline aqueous electrolytes such as sodium hydroxide and potassium hydroxide, etc., but not limited thereto. Preferably, the anolyte is an aqueous solution of sodium hydroxide.

[0021] Further, the electrolysis voltage is -0.1 V to -0.6 V (VS. RHE). Preferably, the voltage is -0.4 V (VS. RHE).

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts a three-step method of wet chemistry - hydrothermal - high-temperature calcination to prepare, for the first time, a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires, effectively improving the ammonia synthesis performance of the catalyst; (2) The yield of the N-CoMoO4 / CuO NW material prepared by the present invention for catalytic reduction of nitrate to ammonia can reach 1.45 mmol h -1 cm -2 or more; (3) The N-CoMoO4 / CuO NW catalyst prepared by the present invention has excellent catalytic stability and does not show obvious attenuation after 8 cyclic stability tests; (4) The N-CoMoO4 / CuO NW catalyst prepared by the present invention has low-cost synthesis raw materials and a simple preparation process, and is suitable for large-scale production.

[0023] Commercially available copper foam is inexpensive and easily available, and is an excellent catalyst support. And CuO nanowires can be obtained by modifying it. CuO nanowires are helpful for the penetration of the electrolyte, the adsorption of reactants and the desorption of products. And CoMoO4, as a donor of active hydrogen, can provide active hydrogen for intermediates during the nitrate reduction process, which is helpful for the deoxygenation and hydrogenation processes of nitrogen-containing intermediates. In addition, by introducing heteroatom nitrogen, the adsorption of NO3 - on the catalyst surface can be further enhanced. Thereby further improving the performance of the catalyst. Therefore, improving the performance of electrochemical catalytic reduction of nitrate to ammonia with a nitrogen-doped cobalt molybdate grown on CuO nanowires as the catalyst is of great significance for the treatment of actual industrial wastewater.

[0024] Under the multiple actions of CuO nanowires and nitrogen atoms, the present invention enhances the adsorption capacity of nitrate on the catalyst surface. Moreover, cobalt molybdate, as a carrier for providing hydrogen protons, enhances the hydrogenation process of nitrogen-containing intermediates and improves the efficiency of nitrate conversion to ammonia. The involved preparation method has low cost and strong operability, and has good application prospects. Description of the Drawings

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only the embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained according to the provided drawings.

[0026] Figure 1 It is the electron scanning microscope image of the N-CoMoO4 / CuO NW-2.5-300 catalyst of the present invention; Figure 2 It is the XRD pattern of the N-CoMoO4 / CuO NW-2.5-300 catalyst of the present invention; Figure 3 It is the comparison chart of the Faraday efficiency and ammonia production rate of catalysts with different doping ratios of sodium molybdate and cobalt nitrate in nitrate reduction; Figure 4 It is the comparison chart of the Faraday efficiency and ammonia production rate of catalysts obtained after being treated at different ammonia calcination temperatures in nitrate reduction; Figure 5 It is the production rate and Faraday efficiency chart of the N-CoMoO4 / CuO NW-2.5-300 catalyst after continuous electrolysis for 8 h. Detailed Embodiments

[0027] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.

[0028] The embodiments of the present invention disclose the preparation and application of a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires.

[0029] To better understand the present invention, the following further specifically elaborates on the present invention through the following embodiments. However, it should not be construed as a limitation to the present invention. For some non-essential improvements and adjustments made by those skilled in the art according to the above invention content, they are also considered to fall within the scope of protection of the present invention.

[0030] Next, in combination with specific embodiments, the technical solution of the present invention will be further described.

[0031] In the following examples, commercial copper foam with an area of 3×4 cm 2 and a thickness of 0.5 mm was used, the hydrochloric acid concentration was 2 M, and ultrasonic pretreatment was carried out for 15 min.

[0032] In the mixed solution of sodium hydroxide and ammonium persulfate, the concentration of the sodium hydroxide solution was 5 M, the concentration of the ammonium persulfate solution was 0.25 M, the mixed volume was 50 mL each, and the soaking time was 30 min.

[0033] The preparation process of the molybdenum-cobalt mixed solution was as follows: equimolar sodium molybdate dihydrate and cobalt nitrate hexahydrate were added to deionized water with a volume of 35 mL, and the stirring rate of the magnetic stirrer was 600 r / min for 5 min. When 2.5 mmol was added to each, the mass of sodium molybdate dihydrate was 0.6048 g, and the mass of cobalt nitrate hexahydrate was 0.7276 g.

[0034] Example 1

[0035] (1) After the commercial copper foam was pretreated with hydrochloric acid, it was washed 2 - 3 times with ethanol and deionized water, and then the copper foam was immersed in the mixed solution of sodium hydroxide and ammonium persulfate for 30 min to obtain Cu(OH)₂ nanowires. The Cu(OH)₂ nanowires were immersed in the mixed solution of Na₂MoO₄·2H₂O and Co(NO₃)₂·6H₂O with a solution volume of 35 mL, and the dosages of Na₂MoO₄·2H₂O and Co(NO₃)₂·6H₂O were both 1.5 mmol. After hydrothermal reaction at 150 °C for 10 h, it was taken out after cooling to room temperature and washed 2 - 3 times with ethanol and deionized water. After vacuum drying, it was placed in a tubular furnace and calcined at 300 °C for 2 h in an ammonia atmosphere and then taken out to obtain N-CoMoO₄ / CuO NW-1.5 (2) The catalyst obtained above was cut into 1×1 cm 2Electrode sheets of a certain size were obtained to form a cathode plate. A commercial platinum sheet was used as the anode plate, and Hg / HgO was used as the reference electrode to form a three-electrode system. 25 mL of a mixed solution of 1 M NaOH and 0.1 M NaNO3 solution was loaded into the cathode cell, and an equal amount of a solution with a NaOH concentration of 1 M was loaded into the anode cell. The switch of the electrochemical workstation was turned on, and the voltage was set to -0.4 V (VS.RHE) and the reaction continued for 25 min. After the reaction, the ammonia concentration was detected by indophenol blue spectrophotometry, and the ammonia production rate and Faraday efficiency were calculated. When the dosages of both Na2MoO4·2H2O and Co(NO3)2·6H2O were 1.5 mmol, the ammonia production rate of the prepared N-CoMoO4 / CuO NW-1.5 was 0.9158 mmol h -1 cm -2 , and the Faraday efficiency was 80.27%.

[0036] Example 2

[0037] (1) After the commercial copper foam was pretreated with hydrochloric acid, it was washed 2 - 3 times with ethanol and deionized water, and then the copper foam was immersed in a mixed solution of sodium hydroxide and ammonium persulfate for 30 min to obtain Cu(OH)2 nanowires. The Cu(OH)2 nanowires were immersed in a mixed solution of Na2MoO4·2H2O and Co(NO3)2·6H2O. The volume of the solution was 35 mL, and the dosages of both Na2MoO4·2H2O and Co(NO3)2·6H2O were 2.5 mmol.

[0038] After hydrothermal reaction at 150 °C for 10 h, it was taken out after cooling to room temperature and washed 2 - 3 times with ethanol and deionized water. After vacuum drying, it was placed in a tubular furnace and calcined at 300 °C for 2 h under ammonia atmosphere and then taken out to obtain N-CoMoO4 / CuO NW-2.5-300; (2) The catalyst obtained above was cut into electrode sheets of 1×1 cm 2 size to obtain a cathode plate. A commercial platinum sheet was used as the anode plate, and Hg / HgO was used as the reference electrode to form a three-electrode system. 25 mL of a mixed solution of 1 M NaOH and 0.1 M NaNO3 solution was loaded into the cathode cell, and an equal amount of a solution with a NaOH concentration of 1 M was loaded into the anode cell. The switch of the electrochemical workstation was turned on, and the voltage was set to -0.4 V (VS.RHE) and the reaction continued for 25 min. After the reaction, the ammonia concentration was detected by indophenol blue spectrophotometry, and the ammonia production rate and Faraday efficiency were calculated. When the dosages of both Na2MoO4·2H2O and Co(NO3)2·6H2O were 2.5 mmol, the ammonia production rate of the prepared N-CoMoO4 / CuO NW-2.5-300 was 1.5863 mmol h -1 cm-2 , The Faraday efficiency is 98.96%.

[0039] Example 3

[0040] (1) After pretreating commercial copper foam with hydrochloric acid, washing it 2 - 3 times with ethanol and deionized water, immerse the copper foam in a mixed solution of sodium hydroxide and ammonium persulfate for 30 min to obtain Cu(OH)₂ nanowires. Immerse the Cu(OH)₂ nanowires in a mixed solution of Na₂MoO₄·2H₂O and Co(NO₃)₂·6H₂O. The volume of the solution is 35 mL, and the dosages of both Na₂MoO₄·2H₂O and Co(NO₃)₂·6H₂O are 3.5 mmol. After hydrothermal reaction at 150 °C for 10 h, cool it to room temperature and take it out, then wash it 2 - 3 times with ethanol and deionized water. After vacuum drying, place it in a tube furnace, calcine it at 300 °C for 2 h in an ammonia atmosphere and then take it out to obtain N-CoMoO₄ / CuO NW-3.5.

[0041] (2) Cut the catalyst obtained above into electrode sheets with a size of 1×1 cm 2 to obtain the cathode plate. Use a commercial platinum sheet as the anode plate and Hg / HgO as the reference electrode to form a three-electrode system. Fill 25 mL of a mixed solution of 1 M NaOH and 0.1 M NaNO₃ solution in the cathode cell, and fill an equal amount of a solution with a NaOH concentration of 1 M in the anode cell. Turn on the switch of the electrochemical workstation, set the voltage to -0.4 V (VS.RHE) and react continuously for 25 min. After the reaction, detect the ammonia concentration by indophenol blue spectrophotometry, and calculate the ammonia production rate and Faraday efficiency. When the masses of both Na₂MoO₄·2H₂O and Co(NO₃)₂·6H₂O are 3.5 mmol, the ammonia production rate of the prepared N-CoMoO₄ / CuO NW-3.5 is 1.2892 mmol h -1 cm -2 , and the Faraday efficiency is 92.39%.

[0042] Example 4

[0043] (1) After pretreating commercial copper foam with 2M hydrochloric acid, washing it 2 - 3 times with ethanol and deionized water, immerse the copper foam in a mixed solution of sodium hydroxide and ammonium persulfate for 30 min to obtain Cu(OH)₂ nanowires. Immerse the Cu(OH)₂ nanowires in a mixed solution of Na₂MoO₄·2H₂O and Co(NO₃)₂·6H₂O. The volume of the solution is 35 mL, and the dosages of both Na₂MoO₄·2H₂O and Co(NO₃)₂·6H₂O are 2.5 mmol.

[0044] After hydrothermal reaction at 150 °C for 10 h, it was taken out after cooling to room temperature and washed 2-3 times with ethanol and deionized water. After vacuum drying, it was placed in a tube furnace and calcined at 200 °C for 2 h in an ammonia atmosphere and then taken out to obtain N-CoMoO4 / CuO NW-200.

[0045] (2) The catalyst obtained above was cut into electrode pieces of 1×1 cm 2 in size to obtain a cathode plate. A commercial platinum sheet was used as the anode plate and Hg / HgO as the reference electrode to form a three-electrode system. 25 mL of a mixed solution of 1 M NaOH and 0.1 M NaNO3 solution was loaded into the cathode cell, and an equal amount of a solution with a NaOH concentration of 1 M was loaded into the anode cell. The switch of the electrochemical workstation was turned on, and the voltage was set to -0.4 V (VS.RHE) and the reaction continued for 25 min. After the reaction, the ammonia concentration was detected by indophenol blue spectrophotometry, and the ammonia production rate and Faraday efficiency were calculated. When the ammonia calcination temperature was 200 °C, the ammonia production rate of the prepared N-CoMoO4 / CuO NW-200 was 1.1728 mmol h -1 cm -2 , and the Faraday efficiency was 85.77%.

[0046] Example 5

[0047] (1) After the commercial copper foam was pretreated with hydrochloric acid, it was washed 2-3 times with ethanol and deionized water, and then the copper foam was immersed in a mixed solution of sodium hydroxide and ammonium persulfate for 30 min to obtain Cu(OH)2 nanowires. The Cu(OH)2 nanowires were immersed in a mixed solution of Na2MoO4·2H2O and Co(NO3)2·6H2O. The volume of the solution was 35 mL, and the dosages of Na2MoO4·2H2O and Co(NO3)2·6H2O were both 2.5 mmol.

[0048] After hydrothermal reaction at 150 °C for 10 h, it was taken out after cooling to room temperature and washed 2-3 times with ethanol and deionized water. After vacuum drying, it was placed in a tube furnace and calcined at 400 °C for 2 h in an ammonia atmosphere and then taken out to obtain N-CoMoO4 / CuO NW-400.

[0049] (2) The catalyst obtained above was cut into electrode pieces of 1×1 cm 2Electrode sheets of a certain size were used to obtain the cathode plate. A commercial platinum sheet was used as the anode plate, and Hg / HgO was used as the reference electrode to form a three-electrode system. 25 mL of a mixed solution of 1 M NaOH and 0.1 M NaNO3 solution was filled in the cathode cell, and an equal amount of a solution with a NaOH concentration of 1 M was filled in the anode cell. The switch of the electrochemical workstation was turned on, and the voltage was set to -0.4 V (VS.RHE) and the reaction continued for 25 min. After the reaction, the ammonia concentration was detected by indophenol blue spectrophotometry, and the ammonia production rate and Faraday efficiency were calculated. When the calcination temperature of ammonia was 400 °C, the ammonia production rate of the prepared N-CoMoO4 / CuO NW-400 was 1.2413 mmol h -1 cm -2 . The Faraday efficiency was 94.46%.

[0050] Comparing Examples 1, 2, and 3, a comparison chart of the Faraday efficiency and ammonia production rate of catalysts with different doping ratios of sodium molybdate and cobalt nitrate in nitrate reduction was obtained, as shown in Figure 3 shown; it can be seen from the figure that with the increase in the doping ratio of sodium molybdate and cobalt nitrate, both the Faraday efficiency and the ammonia production rate first increase and then decrease. The catalyst N-CoMoO4 / CuO NW-2.5-300 in Example 2 achieved the highest Faraday efficiency and ammonia production rate.

[0051] Comparing Examples 4, 2, and 5, a comparison chart of the Faraday efficiency and ammonia production rate of catalysts obtained after treatment at different ammonia calcination temperatures in nitrate reduction was obtained, as shown in Figure 4 shown. It can be seen from the figure that at ammonia calcination temperatures of 200 °C, 300 °C, and 400 °C, with the increase in the calcination temperature, both the Faraday efficiency and the ammonia production rate first increase and then decrease. The catalyst N-CoMoO4 / CuO NW-2.5-300 in Example 2 achieved the highest Faraday efficiency and ammonia production rate.

[0052] The results of the production rate and Faraday efficiency of the N-CoMoO4 / CuO NW-2.5-300 catalyst after continuous electrolysis for 8 h are shown in the following table:

[0053] It can be seen from the above table and Figure 5 that under long-term cyclic testing, the ammonia production rate remained basically unchanged, and the Faraday efficiency decreased slightly, both maintaining high stability.

[0054] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the spirit and scope of the technical solutions of the present invention, and they should all be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires, characterized in that: The steps include: (1) ultrasonically pretreating the copper foam with hydrochloric acid and cleaning it; (2) The pretreated copper foam is immersed in a mixed solution of sodium hydroxide and ammonium persulfate to obtain Cu(OH)2 nanowires, i.e., Cu(OH)2 NW (3) dissolving sodium molybdate dihydrate and cobalt nitrate hexahydrate in deionized water, and stirring to obtain a molybdenum-cobalt mixed solution; (4) The molybdenum-cobalt mixed solution is transferred to a high-pressure reactor, and the Cu(OH)2 nanowires are vertically immersed therein. A hydrothermal reaction was performed. After the reaction was completed, the mixture was cooled to room temperature, taken out, and washed to obtain a cobalt molybdate catalyst grown on CuO nanowires, namely CoMoO4 / CuO NW; (5) Placing the cobalt molybdate catalyst grown on the CuO nanowires in a tubular furnace, pre-passing ammonia gas, and maintaining the temperature at 200-400° C. to obtain a nitrogen-doped cobalt molybdate catalyst grown on the CuO nanowires, namely, N-CoMoO4 / CuO NW.

2. The method for preparing a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires according to claim 1, characterized in that: In the step (1), the concentration of hydrochloric acid is 1-3 M, and the ultrasonic time is 10-20 min.

3. The method for preparing a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires according to claim 1, characterized in that: In the step (2), the concentration of the sodium hydroxide solution in the mixed solution of sodium hydroxide and ammonium persulfate is 4-6 M, and the concentration of the ammonium persulfate solution is 0.2-0.3 M; and the immersion time in the mixed solution of sodium hydroxide and ammonium persulfate is 20-40 min.

4. The method for preparing a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires according to claim 1, characterized in that: In the step (3), the molar concentrations of sodium molybdate and cobalt nitrate in the molybdenum-cobalt mixed solution are equal, which is (1.5-3.5) mmol / 35 ml.

5. The method for preparing a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires according to claim 1, characterized in that: In the step (4), the temperature of the hydrothermal reaction is 120-160° C., and the hydrothermal reaction time is 8-12 hours.

6. The method for preparing a nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires according to claim 1, characterized in that: In the step (5), the temperature is raised to 200-400° C. at 5° C. / min in an ammonia atmosphere and kept at this temperature for 1-3 h.

7. A nitrogen-doped cobalt molybdate catalyst grown on CuO nanowires, characterized in that: The method is prepared by any one of claims 1 to 6.

8. The use of the nitrogen-doped cobalt molybdate catalyst according to claim 7, characterized in that: The nitrogen-doped cobalt molybdate catalyst is used in the production of ammonia by reducing nitrate.

9. The use of the nitrogen-doped cobalt molybdate catalyst according to claim 8, characterized in that: The process of applying the nitrogen-doped cobalt molybdate catalyst to nitrate reduction to produce ammonia is as follows: A sodium hydroxide solution is prepared as an anolyte, and a mixed solution of sodium hydroxide and sodium nitrate is prepared as a catholyte; Hg / HgO is used as a reference electrode, and the nitrogen-doped cobalt molybdate catalyst is used as a cathode plate; the cathode plate, the anode plate, and the reference electrode are assembled together into a three-electrode electrolysis system, and the cathode is filled with cathode liquid, and the anode is filled with an equal amount of anode liquid on both sides of an H-type electrolytic cell, and an electrolysis voltage is set to perform electrolysis; the electrolysis voltage is -0.1 V ~ -0.6 V (VS. RHE).

10. The use of the nitrogen-doped cobalt molybdate catalyst according to claim 9, characterized in that: The concentration of the sodium hydroxide solution is 1 M. In the mixed solution of sodium hydroxide and sodium nitrate, the concentration of sodium hydroxide is 1 M, and the concentration of sodium nitrate is 0.1 M.